Digital Age Education Management Strategies in Facing Global Changes in Islamic Education - Muhamad Hamsan Wadi; Rusli Malli; Muammar Asykur (Al-Qalam Institute, 2023)
This study aims to explore the impact of the use of digital technology on improving the quality of learning in Islamic-based junior high schools, as well as analyze the role of teacher competency development in facing global changes. This research is based on the rapid development of digital technology that has changed the way of learning and communication in the world of education, especially in the Islamic education environment. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation in the field. The findings were analyzed based on the Miles and Huberman model. The results show that the application of digital platforms such as e-learning and social media has increased learning flexibility, expanded educational reach, and strengthened data-based evaluation systems. In addition, teacher training to improve digital literacy has proven to be important in ensuring effective technology adaptation. The findings are expected to contribute by providing new insights into the importance of digitalization in Islamic education management, as well as underlining the role of teacher training in supporting learning effectiveness in the digital era.